Petitions Systems: Outcomes, 'Success' and 'Failure'. Issue 2 (3rd January 2019) - Bochel, Catherine
Abstract: The use of formal petitions systems has become increasingly widespread in the UK. The systems in the National Assembly for Wales and the Scottish Parliament have been widely seen as models of good practice. However, one aspect that has not been explored in sufficient depth is the outcomes of petitions. This article uses petitions to the two legislatures to develop a framework to assist in understanding how 'success' and 'failure' might be judged in relation to petitions. In addition to contributing to our wider understanding of such systems, this may help political institutions think about the processes which underpin their petition systems, the ways in which they frame the systems for the public, and could help better manage petitioner expectations, including by illustrating to petitioners what they might achieve at different stages in the petitions process.